2017
DOI: 10.1016/j.sjopt.2017.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Magnitude of diabetes and hypertension among patients with Dry Eye Syndrome at a tertiary hospital of Riyadh, Saudi Arabia – A case series

Abstract: This series in central Saudi Arabia suggests that the magnitude of chronic diseases such as diabetes, hypertension, obesity and dyslipidemia seems to be higher in patients with DES compared to the population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 26 publications
2
6
0
Order By: Relevance
“…[311] Age, gender, diabetes, hypertension, glaucoma, and topical medication are known risks factors for DED. [121314] However, studies in the past have not shown conclusive association and special relationship of these factors to DED. [1315]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[311] Age, gender, diabetes, hypertension, glaucoma, and topical medication are known risks factors for DED. [121314] However, studies in the past have not shown conclusive association and special relationship of these factors to DED. [1315]…”
Section: Introductionmentioning
confidence: 99%
“…[121314] However, studies in the past have not shown conclusive association and special relationship of these factors to DED. [1315]…”
Section: Introductionmentioning
confidence: 99%
“…Globally, DED is more prevalent among females [ 2 , 6 ], with a similar finding in Saudi Arabia [ 3 ]. Other than female gender predominance, risk factors include old age [ 7 ], blepharitis [ 5 ], smoking [ 5 ] and having a chronic disease such as diabetes mellitus, arthritis and hypercholesterolemia [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…11 Additionally, DM is also a major cause of ocular complications including diabetic retinopathy, diabetic papillopathy, glaucoma, cataract, and ocular surface diseases such as diabetic keratopathy and dry eye syndrome. 12,13 Dry eye syndrome, also known as Keratoconjunctivitis sicca, is one of the most common ocular disorders throughout the world. 14 It is a complex disease of the anterior surface of the eye and results in tear film deficiency, significantly hindering the performance of daily life and may lead to blindness in severe cases.…”
Section: Introductionmentioning
confidence: 99%